The Association Between Parenting Styles and Emotional Intelligence in Early Childhood - Trejo, Sharie; Jannah, Isratul (Journal of Foundational Learning and Child Development, 2025)
Purpose of the study: This study aimed to examine the relationship between different parenting styles (authoritative, authoritarian, and permissive) and the development of emotional intelligence in early childhood. Materials and methods: The study involved 27 male junior high school students from Medan city, Indonesia. A quantitative non-experimental design with a correlational approach was employed. Participants completed the Parenting Practices Questionnaire (PPQ) to assess parenting styles and the Sullivan Emotional Intelligence Scale for Children (EISC) to measure emotional intelligence. Statistical analysis was performed using SPSS version 25. Results: Findings revealed that authoritative parenting style had a significant positive correlation with emotional intelligence (r = 0.512, p < 0.001). Conversely, authoritarian parenting demonstrated a significant negative correlation with emotional intelligence (r = -0.347, p < 0.05), while permissive parenting showed a weak negative correlation (r = -0.215, p < 0.05). Conclusions: Parenting styles significantly influence the development of emotional intelligence in early childhood. Authoritative parenting, characterized by high responsiveness and reasonable demands, appears to foster higher levels of emotional intelligence compared to authoritarian and permissive styles